Perspectives In Competencies-Based Education: A Curricular Experience To Form A New Industrial Design Profile - Betancourt Velasco, María Clara; Mejía Puig, Luis Alfonso; 15th International Conference on Engineering and Product Design Education (Institution of Engineering Designers, The Design Society, 2013)
There is an evident gap between the quality of the design graduates and what future employers want them to do, it is understood that there is a difference between what they learn in school and what they are required to do in a professional setting. That is why todayâ s designer needs multiple abilities to develop innovative projects in varied contexts. This implies that it is necessary to implement changes in the scope and structure of the design curricula. A methodology was used that helped create a designer profile and a new curriculum proposal with entrepreneurial skills, the capability to identify business opportunities and the ability to manage a design project
Keywords: Competencias; Plan de estudios; Espíritu empresarial; Habilidades; Diseño industrial; Industrial design